2013
DOI: 10.1186/1756-9966-32-5
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of combined gene therapy expressing constitutive human GM-CSF and hyperthermia-regulated human IL-12

Abstract: BackgroundAn adenovirus that expresses both interleukin (IL)-12 and granulocyte-macrophage colony-stimulating-factor (GM-CSF) has been proven to be very effective in treating several tumors, but causes serious normal tissue toxicities.MethodsIn this study, a novel adenoviral vector was constructed by placing the human GM-CSF gene under the control of the CMV-IE promoter and human IL-12 gene under the control of heat shock protein 70B gene promoter. Both hGM-CSF and hIL-12 expressions in virus-infected tumor ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…One of such means is activators of the host immune system, such as cytokines [82-84]. We used GM-CSF for this goal.…”
Section: Discussionmentioning
confidence: 99%
“…One of such means is activators of the host immune system, such as cytokines [82-84]. We used GM-CSF for this goal.…”
Section: Discussionmentioning
confidence: 99%
“…Such a pessimistic situation is largely ascribable to the underappreciated pathogenesis of lung cancer. Up to recent, multitudinous studies have verified the principal roles of various genetic abnormalities in the development of lung cancer, which finally appear as the dysfunctions of numerous proteins [ 3 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Wei et al [ 25 ] demonstrated HSP70B-driven expression of 1L-12 using adenovirus. Mice with subcutaneous Hep3B tumors were given an intratumoral injection of adenovirus encoding both heat inducible IL-12 and constitutively expressed granulocyte macrophage colony stimulating factor (GM-CSF).…”
Section: Introductionmentioning
confidence: 99%